2013
DOI: 10.1177/0022042613491099
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Drug Use Functions and Risk Reduction Practices Among High-Risk Nonmedical Users of Prescription Drugs

Abstract: Nonmedical use of prescription drugs has become the fastest growing drug problem in the United States, particularly among young adults. This study examines the reasons young polydrug users misuse prescription drugs, and explores how young users employ risk reduction strategies to minimize adverse consequences. The sample was recruited during 2008 and 2009 in Los Angeles and New York, and comprised 45 nonmedical users of prescription drugs, aged 16 to 25. Data from a semistructured interview were analyzed quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
(59 reference statements)
1
20
0
3
Order By: Relevance
“…1113 As a result, young adult NMPO users are at increasingly high risk of adverse health outcomes, such as rising rates of unintentional overdose, transition to heroin use, and acquiring hepatitis C (HCV) or HIV infection. 11,12,14–17 Thus, understanding the context and perspectives of NMPO use among young adults may help to inform programs and policies designed to reduce negative health impacts (such as accidental overdose or transition to opioid dependence) for young adult NMPO users and persons in their social networks.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…1113 As a result, young adult NMPO users are at increasingly high risk of adverse health outcomes, such as rising rates of unintentional overdose, transition to heroin use, and acquiring hepatitis C (HCV) or HIV infection. 11,12,14–17 Thus, understanding the context and perspectives of NMPO use among young adults may help to inform programs and policies designed to reduce negative health impacts (such as accidental overdose or transition to opioid dependence) for young adult NMPO users and persons in their social networks.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…The role of motives for prescription drug misuse among young adults, which has been investigated in prior quantitative and qualitative studies, varies depending on the type of prescription drug. For example, the most commonly cited reasons for misuse of opioids include self-medicating to relive pain, to get high, to relax, to experiment, or to monitor the intake of other substances (McCabe et al, 2007; McCabe, West, & Boyd, 2013; Zachny & Lichtor, 2008; Silva, Kecojevic, & Lankenau, 2013). Tranquilizers or benzodiazapines are often misused for their therapeutic indication, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They are also the second most common drug class through which Americans are initiated into illicit drug use; while 2.4 million Americans over the age of 12 were initiated into illicit drug use through marijuana in 2013, 1.5 million people reported that the first drug they ever tried was a PO (SAMHSA, 2014). Research has found that young adults frequently use POs nonmedically with peers in social settings (e.g., at parties, while hanging out with friends) and young people report using POs to reduce anxiety, facilitate social interactions, enhance sexual experiences, and intensify the effects of other substances (Mateu-Gelabert, Guarino, Jessell, & Teper, 2015; McCabe, Cranford, Boyd, & Teter, 2007; Silva, Kecojevic, & Lankenau, 2013). When taken in large doses or in combination with other substances (e.g., benzodiazepines, alcohol), the effects of POs may lead to drowsiness, impaired judgment, incapacitation, loss of consciousness, and overdose (Frank etal., 2015; Jones, Mogali, & Comer, 2012; Lipman, 2010; Mateu-Gelabert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%